Clinical Significance of Circulating Osteopontin Levels in Patients With Lung Cancer and Correlation With VEGF and MMP-9. (13th September 2016) - Kerenidi, Theodora; Kazakou, Aikaterini P.; Lada, Martha; Tsilioni, Irini; Daniil, Zoe; Gourgoulianis, Konstantinos I.
ABSTRACT: Osteopontin (OPN) is a multifunctional cytokine involved in carcinogenesis. Serum levels of OPN, vascular endothelial growth factor (VEGF), and matrix metalloproteinase-9 (MMP-9) were measured by ELISA in 90 lung cancer patients. OPN levels were elevated in patients compared to controls ( p <.0001). Smokers, patients with worse performance status, and weight loss exhibited higher OPN levels ( p =.0012, .00036, and.0003, respectively). Increased OPN levels were associated with worse survival ( p =.0018). Finally, OPN levels were positively correlated with both VEGF ( p =.0008) and MMP-9 ( p <.0001). OPN might serve as a prognostic biomarker, and the positive correlation between OPN and both VEGF and MMP-9 could implicate new insights in tumor angiogenesis.